2023
DOI: 10.1126/sciadv.adg4993
|View full text |Cite
|
Sign up to set email alerts
|

ULK1-mediated metabolic reprogramming regulates Vps34 lipid kinase activity by its lactylation

Abstract: Autophagy and glycolysis are highly conserved biological processes involved in both physiological and pathological cellular programs, but the interplay between these processes is poorly understood. Here, we show that the glycolytic enzyme lactate dehydrogenase A (LDHA) is activated upon UNC-51–like kinase 1 (ULK1) activation under nutrient deprivation. Specifically, ULK1 directly interacts with LDHA, phosphorylates serine-196 when nutrients are scarce and promotes lactate production. Lactate connects autophagy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 61 publications
(73 reference statements)
1
12
0
Order By: Relevance
“…Indeed, HEK293T cells treated with various concentrations of lactate showed a dose-dependent induction of α-tubulin lactylation (Extended Data Fig. 3a, b), consistent with previous reports indicating that lactate enhances protein lactylation 27,32,35,44 . Similarly, GSKA, an inhibitor of lactate dehydrogenase (LDH) designed to prevent lactate production, reduced α-tubulin lactylation (Extended Data Fig.…”
Section: Hdac6 Is Required For Metabolic Regulation Of α-Tubulin Lact...supporting
confidence: 90%
See 2 more Smart Citations
“…Indeed, HEK293T cells treated with various concentrations of lactate showed a dose-dependent induction of α-tubulin lactylation (Extended Data Fig. 3a, b), consistent with previous reports indicating that lactate enhances protein lactylation 27,32,35,44 . Similarly, GSKA, an inhibitor of lactate dehydrogenase (LDH) designed to prevent lactate production, reduced α-tubulin lactylation (Extended Data Fig.…”
Section: Hdac6 Is Required For Metabolic Regulation Of α-Tubulin Lact...supporting
confidence: 90%
“…HDAC6 functions as a primary "writer" for α-tubulin lactylation Previous studies have indicated that acetyltransferases may also catalyze protein lactylation 27,29,32 . To identify the protein responsible for α-tubulin lactylation, we transfected various acetyltransferases into HEK293T cells and assessed α-tubulin lactylation levels.…”
Section: Identi Cation Of α-Tubulin Lactylation On K40mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, it has been reported that the timed degradation of lactate‐kinetic cell cycle proteins directly regulates protein function, thereby controlling the biochemical mechanisms of cell cycle and proliferation 57 . Furthermore, lactate mediates lactylation modification of type III phosphatidylinositol kinase (Vps34) lysine catalyzed by acyltransferases, thereby increasing its kinase activity, which in turn promotes the occurrence of autophagy and the endosomal‐lysosomal degradation pathway 58 . Notably, as a metabolite and regulator of the central nervous system, lactate has a wide range of effects on neurodegenerative diseases 59 .…”
Section: Discussionmentioning
confidence: 99%
“…57 Furthermore, lactate mediates lactylation modification of type III phosphatidylinositol kinase (Vps34) lysine catalyzed by acyltransferases, thereby increasing its kinase activity, which in turn promotes the occurrence of autophagy and the endosomal-lysosomal degradation pathway. 58 Notably, as a metabolite and regulator of the central nervous system, lactate has a wide range of effects on neurodegenerative diseases. 59 In this study, we observed that VGLL4 promoted lactate production while concurrently reduced APP amyloidogenic processing and ameliorated neuronal synaptic damage (Figures 3 and 5).…”
Section: Discussionmentioning
confidence: 99%